Thermal and thermodynamic characterization of a dye powder from liquid turmeric extracts by spray drying (2016)
This study aimed to evaluate the thermodynamic properties of sorption isotherms and glass transition temperature (Tg) and the thermal properties of a dye powder obtained from turmeric extracts using spray drying. The sorption isotherms were evaluated at 15, 25 and 35 ºC using the dynamic gravimetric method, wherein the isotherm data of the experiment were fit to GAB and BET models. Likewise, the Tg was measured using differential scanning calorimetry (DSC). Thermogravimetric analysis (TGA) was used to determine the mass loss, and the thermal properties (heat capacity, diffusivity and thermal conductivity) were determined using transient flow method. The results demonstrated that the GAB model best fit the adsorption data. The DSC analysis presented a glass transition temperature of 65.35 ºC and a loss of volatiles at 178.07 ºC. The TGA analysis indicated a considerable mass loss starting at 193 ºC, resulting in degradation of the product. The thermal properties demonstrated a heat capacity of 2.45 J/g ºC, a thermal conductivity of 0.164 ±0.001 W/mK and a thermal diffusivity of 8.7x10-8 ± 0.000 m2/s